The Consumer in Cross-Border Passing Off Cases - Austin, Graeme W (Victoria University of Wellington Law Review, 2016)
This article considers Starbucks (HK) Ltd v British Sky Broadcasting Group [2015] UKSC 31 in which the Supreme Court of the United Kingdom held that, for the purposes of the passing off tort, goodwill is strictly territorial. It compares this approach with that of New Zealand cases which have adopted a more flexible approach to the protection of goodwill in the cross-border context. The article suggests that, in some cases, the New Zealand approach will be better adapted to consumer experience in the modern international marketplace.